STUDY THE EFFECT OF ENGLISH LANGUAGE TO SCIENCE IN UZBEKISTAN (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In the 21st century, science is developing very rapidly all over the world. Especially developed countries, including European countries, America, Japan, surprise the whole world with their advanced technologies and innovations. It should be remembered that almost all the news today is published in English. Learning English is developing on a large scale in Uzbekistan.